The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-30165-2
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced impairment of endothelial function in track and field female athletes

Abstract: Professional athletes are often exposed to high training loads that may lead to overfatigue, overreaching and overtraining that might have a detrimental effects on vascular health. We determined the effects of high training stress on endothelial function assessed by the flow-mediated dilation (FMD) and markers of glycocalyx shedding. Vascular examination as well as broad biochemical, hormonal and cardiometabolic evaluation of sprint and middle-distance female runners were performed after 2 months of preparator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 69 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…39 Additionally, the basal level of matrix metalloproteinase 1 increased in response to resistance training in female track-andfield athletes, an enzyme responsible for glycocalyx degradation and endothelial dysfunction. 15 It has previously been demonstrated that deloading periods play an important role in reducing arterial stiffening, as seen in healthy male and female adults over 16 weeks compared to controls who continued to increase the load during deloading weeks. 40 Thus, poor resistance training regimens could be detrimental to vascular health in women's rugby sevens athletes.…”
Section: Resistance Trainingmentioning
confidence: 98%
See 4 more Smart Citations
“…39 Additionally, the basal level of matrix metalloproteinase 1 increased in response to resistance training in female track-andfield athletes, an enzyme responsible for glycocalyx degradation and endothelial dysfunction. 15 It has previously been demonstrated that deloading periods play an important role in reducing arterial stiffening, as seen in healthy male and female adults over 16 weeks compared to controls who continued to increase the load during deloading weeks. 40 Thus, poor resistance training regimens could be detrimental to vascular health in women's rugby sevens athletes.…”
Section: Resistance Trainingmentioning
confidence: 98%
“…Hormonal responses have been previously examined in teamsport athletes, and recent evidence suggests these responses could impair endothelial function. 15 Hormonal markers, like testosterone, are used to determine excessive training loads in athletes by comparing them to cortisol levels. 49 This is commonly referred to as the anabolic-catabolic hormone ratio and has a strong correlation with FMD, an index of endothelial dysfunction.…”
Section: Anabolic and Catabolic Markersmentioning
confidence: 99%
See 3 more Smart Citations